Exercise-induced muscle damage is reduced in resistance-trained males by branched chain amino acids: a randomized, double-blind, placebo controlled study - Howatson Glyn; Hoad Michael; Goodall Stuart; Tallent Jamie; Bell Phillip G; French Duncan N (Taylor & Francis Group, 2012)
Abstract Background It is well documented that exercise-induced muscle damage (EIMD) decreases muscle function and causes soreness and discomfort. Branched-chain amino acid (BCAA) supplementation has been shown to increase protein synthesis and decrease muscle protein breakdown, however, the effects of BCAAs on recovery from damaging resistance training are unclear. Therefore, the aim of this study was to examine the effects of a BCAA supplementation on markers of muscle damage elicited via a sport specific bout of damaging exercise in trained volunteers. Methods Twelve males (mean ± SD age, 23 ± 2 y; stature, 178.3 ± 3.6 cm and body mass, 79.6 ± 8.4 kg) were randomly assigned to a supplement (n = 6) or placebo (n = 6) group. The damaging exercise consisted of 100 consecutive drop-jumps. Creatine kinase (CK), maximal voluntary contraction (MVC), muscle soreness (DOMS), vertical jump (VJ), thigh circumference (TC) and calf circumference (CC) were measured as markers of muscle damage. All variables were measured immediately before the damaging exercise and at 24, 48, 72 and 96 h post-exercise. Results A significant time effect was seen for all variables. There were significant group effects showing a reduction in CK efflux and muscle soreness in the BCAA group compared to the placebo (P<0.05). Furthermore, the recovery of MVC was greater in the BCAA group (P<0.05). The VJ, TC and CC were not different between groups. Conclusion The present study has shown that BCAA administered before and following damaging resistance exercise reduces indices of muscle damage and accelerates recovery in resistance-trained males. It seems likely that BCAA provided greater bioavailablity of substrate to improve protein synthesis and thereby the extent of secondary muscle damage associated with strenuous resistance exercise. Clinical Trial Registration Number: NCT01529281.